Optimizing Equipment Layout with ARC and 5S in a Metal Casting Molding Division - Arinda Soraya Putri; Pujji Hastuti; Afiqoh Akmalia Fahmi; Eko Setiawan; Fadhilla Tri Nugrahaini; Much Djunaidi; Bayu Permana; Riva'i Arva Irianto (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2026)
A metal casting manufacturing company operating in Ceper, Klaten. One of the key areas in its production process is the molding division, where casting molds are made. Several issues were identified in this area, including poor organization, inadequate cleanliness, and insufficient attention to workplace safety. This study aims to evaluate the implementation of the 5S culture (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) in the molding division and to propose improvements to enhance four key principles: effectiveness, efficiency, productivity, and occupational safety. Based on the results of the 5S questionnaire data analysis, the overall implementation level was relatively low at 52.78%, with Seiso scoring the highest (66%), followed by Shitsuke (57%), Seiri (54%), Seiton (51%), and Seiketsu (35%). To address these issues, several improvements were proposed, including procedures for item sorting, equipment labeling, implementation of workplace signage, development of Standard Operating Procedures (SOP) for machines, scheduling of machine/tool maintenance, and the establishment of a reward and punishment system. These efforts were further supported by optimizing the workplace layout using the Activity Relationship Chart (ARC) method. The implementation of these improvements resulted in a significant increase in the utilization of the production area, from 33% to 66%.